PENGARUH IKLAN YOUTUBE TRANSPORTASI ONLINE TERHADAP KEPUTUSAN KONSUMEN GOJEK DI WILAYAH KELAPA GADING, JAKARTA UTARA - Dra. Maria F. Lies Ambarwati, M.M. (STARKI, 2020)
The use of proper communication in marketing online transportation services is needed by companies in order to be able to compete against competitors in similar business categories. One of the marketing communication activities that is considered to have the main power to reach large numbers of customers and can persuade consumers is by serving advertisements related to the products offered. This study aims to analyze the effect of YouTube advertising from Gojek online transportation on consumer decisions. The theories and concepts used in this study are persuasion communication theory, marketing communication, AIDA concept, and consumer decision theory. This study was conducted in February-June 2020. The research method used is a quantitative method in the form of a survey with a questionnaire as a tool in data collection and measured using a Likert scale. The sampling technique used was non-probability sampling, namely purposive sampling. The number of respondents is 100 (one hundred) who live in Kelapa Gading, North Jakarta. Researchers tested the validity, reliability, normality, linearity, simple regression, determination, simple correlation, and t test using the SPSS 26 for windows program. The results of the analysis of determination obtained 44.5% which indicates a positive influence between advertising on consumer decisions. The remaining 55.5% is influenced by other variables outside of this study.